2015
DOI: 10.1007/s00405-015-3741-3
|View full text |Cite
|
Sign up to set email alerts
|

Redesign and treatment planning orbital floor reconstruction using computer analysis anatomical landmarks

Abstract: Orbital floor fractures are one of the most commonly encountered maxillofacial fractures due to their weak anatomical structure. Restoration of the orbital floor following a traumatic injury or a tumor surgery is often difficult due to inadequate visibility and lack of knowledge on its anatomical details. The aim of this study is to investigate the locations of the inferior orbital fissure (IOF), infraorbital groove (G), and infraorbital foramen (Fo) and their relationship with the orbital floor using a softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…By two different procedures we evaluated the function of the infra orbital nerve which included pin prick test and electrical pulp testing we found that, there was significant difference between the two groups (P= 0.020 and 0.005 respectively). This in agreement with the study of Ozer et al 2016 (11) who reported that the recovery of the infra orbital nerve function need precise reduction he was evaluated with two different procedures which included electrical detection threshold and pin prick method. At 1 month time, post operatively 50% patients having electrical hyperesthesia when test with electrical detection threshold.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…By two different procedures we evaluated the function of the infra orbital nerve which included pin prick test and electrical pulp testing we found that, there was significant difference between the two groups (P= 0.020 and 0.005 respectively). This in agreement with the study of Ozer et al 2016 (11) who reported that the recovery of the infra orbital nerve function need precise reduction he was evaluated with two different procedures which included electrical detection threshold and pin prick method. At 1 month time, post operatively 50% patients having electrical hyperesthesia when test with electrical detection threshold.…”
Section: Discussionsupporting
confidence: 90%
“…The differences between two sites were found to be significant statistically (p=0.05). Although there is no international consensus on the ideal material to be used for orbital reconstruction (11). However, in our study the success of orbital fracture repair depends not only on the use of material that restores the premorbid orbital volume and shape, but also the capacity to visualize the geometry of the bony defect spatially and to place the titanium mesh to fit the original contour with no evidence of inflammatory and fibrogenic response to the surrounding tissue.…”
Section: Discussionmentioning
confidence: 85%
“…There are many bone [2,12,18,20,38,45,53,57,58,60,66,68] and cadaver [6,14,25,39,44,59,66,71] studies in which the relationship between morphometry of IOG, IOC, and IOF and their relations to the surrounding structures have been examined. Kazkayasi et al [38] evaluated 35 dry skulls both in bones and cephalometric radiography.…”
Section: Discussionmentioning
confidence: 99%
“…The Rhi–FMO and N–FMO distances are of real help in the case of lateral orbital wall fractures when the restoration of the orbital contour as accurately as possible offers superior aesthetic results. Other points, segment or angle measurements would be required for orbital reconstruction, especially for the orbital floor [ 27 ]. For results with a satisfactory accuracy, the relationship of bone structures with the periorbital soft tissues should not be ignored [ 28 ].…”
Section: Discussionmentioning
confidence: 99%